https://doi.org/10.36873/agp.v20: UJI DAYAHAMBAT EUGENOL DARI DAUN CENGKEH HASIL FRAKSINASI TERHADAP PERTUMBUHAN JAMUR PATOGEN Fusarium oxysporum f.sp. Cubense Eugenol Inhibitory Test From Clove Leaf Fractionation Of Fungal Patogen Growth Fusarium oxysporum f.sp. cubense, Juniawan1) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTThis study aims to determine the inhibition of eugenol derived from fractionation clove leaf essentialoils (CLEO) on the growth of pathogenic fungus Fusarium oxysporum f. sp. cubense (Foc) and LC50(Lethal Concentration 50). This research was in vitro, started with purification of clove leaf essentialoil, fractionation by vacuum distillation and bioassay. In vitro tests include exploration of minimuminhibition and preventability tests. Data were analyzed with Microsoft Excel 2010 program. Theresults of minimum inhibition showed at 218,75 ppm concentration of each level was able to inhibitthe growth of Foc fungi. The minimum inhibition exploration was carried out at 218,75 ppm, 109,38ppm, 54,69 ppm and 27,34 ppm. Exploration results showed that fractionated CLEO has been able toinhibit the growth of Foc fungi at 27,34 ppm in the amount of 15,60%. This concentration is used asthe lowest concentration in the inhibitory test. Furthermore, the inhibitory test was carried out startingat the highest concentration of 218,75 ppm, 109,38 ppm, 54,69 ppm and 27,34 ppm. Observationswere made for 7 days after inoculation (DAI). The results showed the best inhibition was at aconcentration of 218,75 ppm at 90,70% and LC50 at 11.17 µL.Keywords: CLEO, fractionation, Foc, in vitro test and LC50